Creation Studies: The Beginning of Heaven and Earth based on Genesis 1:1-2 - Laana, Darwis; Laana, Timothius Theodoris (STT INDONESIA MANADO, 2021)
The study of the creation of an issue that is often discussed by both scientists and theologians. Many theories have been put forward by scientists and include the gap theory beginning in Genesis 1:1-2. The phenomena of this theory of creation have become familiar things because they have been studied in educational benches. As Christians believe that the statement is complete as recorded in Genesis 1:1-2, but not a few are still in a dilemma because these theories are constantly evolving. The focus of this research is the Study of Creation: The Beginning of Heaven and Earth based on Genesis 1:1-2. This paper aims to provide answers to the phenomena that occur regarding the studies made in the study of 1:1-2 incident text studies. The research method used is qualitative. The type of concept article is the result of thought or analysis of emerging phenomena. The results of this study are that: These theories essentially deny the existence of a Creator and Creator of His Work and Omnipotence. Everything that happens by itself and through a very long process, and these theories still have weaknesses that cannot be proven. Contrary to what the Bible says. The book of Genesis tells the story of God's creation. The creation of everything that did not yet exist came into being. This Creator is a part of God's statement which states that the world and everything in it was created by God in six days. And also in the occurrence of verses 1 and 2 there is not a long time gap but one unit.